(untitled) (Third Sector Social Economic Review, 2019)
Cooperatives have been a driving force as a locomotive that has developed and developed with a long history. Cooperatives, a system based on solidarity and solidarity in the economic development of countries, is organized in various fields. One of these areas is the food sector. If the geographically indication products, which reflect the cultures and identities of the countries and which are an effective factor in the domestic tourism and foreign tourism movement, are evaluated within the cooperative system, both the people who produce them and the consumers who will buy them will have economic advantages. As a result of the literature review, it was determined that the primary problem of geographically indication products is inspection. The aim of this study is to present a model related to the audit problem in the evaluation of geographically indication products within the cooperative system. In this direction for the inspection of geographical indications internal and external audit system formed by the cooperative system can be utilized.